Water quality concentration trends and loads identify management needs in the Lake Wister watershed. Issue 1 (8th February 2022) - Lasater, Abbie; Haggard, Brian
Abstract: Trend analyses of water quality seek to determine whether concentrations of constituents have increased or decreased over time, which can show the effectiveness of management practices or the need for pollutant reduction. The Poteau River watershed (PRW) is a transboundary watershed across Arkansas and Oklahoma and, in Arkansas, has been listed as a priority watershed within the Arkansas Nonpoint Source Pollution Plan since 1998. The Poteau River, Black Fork, and Fourche Maline within the PRW flow into Lake Wister, which is an important reservoir for recreation, fishing, and waterfowl hunting for residents and tourists around eastern Oklahoma. The purpose of this study was to analyze long‐term concentration trends and loads on the major tributaries entering Lake Wister using the Weighted Regression on Time, Discharge, and Season (WRTDS). The largest magnitude of loads came from the Poteau River, but flow normalized (FN) P and sediments have decreased over time, which is a positive impact of watershed management and must be maintained. However, FN N on the Poteau River has increased over time and should be the focus of future management on the Poteau River. Although the magnitude of constituent loads from the Fourche Maline is less than from the Poteau River, increasing FN P is a concern and should be prioritized for management in Oklahoma. The relatively undisturbed Black Fork watershed contributes the smallest loads to Lake Wister, and FN concentrations are decreasing or not changing over time, suggesting a low priority for the Black Fork watershed. Core Ideas: The Poteau River contributes the largest loads to Lake Wister. Nitrogen is increasing and must be managed on the Poteau River in Arkansas. Phosphorus is increasing and must be managed on the Fourche Maline in Oklahoma. The mostly forested Black Fork watershed is a low priority for management.